Experiences of living with a sexually transmitted disease: A cross-sectional descriptive survey. (June 2019) - Haapa, Toni; Suominen, Tarja; Koivisto, Anna-Maija; Kylmä, Jari
Some dimensions such as stigmatization have been identified in the previous literature regarding experiences of living with a sexually transmitted disease (STD). However, relatively little is known about the generic experiences of those infected. The aim of this study was to describe the experiences of living with an STD, as evaluated by those infected. Data ( n  = 213) were collected via an online questionnaire and analysed using statistical methods. The experiences of living with an STD varied overall. The immutability of everyday life, a thirst for knowledge, a responsible attitude towards treatment of an STD and the dilemma of disclosing the STD were considered to best describe the experiences of living with an STD. The most recently diagnosed STD and its phase were most often statistically significantly associated with the experiences. We conclude that the diversity of these experiences should be recognized in healthcare, and used in the prevention of STDs.